A Performance Analysis of Sawmills in Oregon from 2003 to 2017. Issue 4 (27th April 2021) - Sun, Changyou; Marcille, Kate C; Daniels, Jean M
Abstract: The number of mills and employees in Oregon's sawmill sector has continuously declined from 2003 to 2017, but the amount of lumber produced has stabilized in recent years. In this study, the performance of individual sawmills is evaluated by applying data envelopment analysis on a unique dataset for 146 mills over four survey years of 2003, 2008, 2013, and 2017. The scale efficiency of these mills is generally high, but their overall technical efficiency is only 85%. In 2017, the most efficient mills as a group used 14% fewer employees, processed 18% more sawlogs, and produced 32% more lumber than an average mill in Oregon. Across the four survey years, productivity growth over time is small at only 0.14% per year, and most of the growth can be attributed to changes in technology. The catch-up effect by individual mills is actually negative at −0.07% per year. These findings reveal that the growth of production efficiency in Oregon's sawmill sector has been slow, and the direction for future improvement relies on better management of operations and resources by individual mills.